2016
DOI: 10.1002/lt.24324
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of simeprevir plus sofosbuvir with or without ribavirin in patients with decompensated genotype 1 hepatitis C cirrhosis

Abstract: Combination antiviral therapy involving sofosbuvir (SOF) and simeprevir (SIM) is a treatment option in patients with genotype 1 chronic hepatitis C; however, the safety of this regimen in patients with decompensated cirrhosis is not established. Data from a combined treatment cohort of 2 large hepatology referral centers were evaluated to assess for safety and efficacy of SIM plus SOF with or without ribavirin (RBV) in patients with Child B or C cirrhosis. All (n 5 42) patients included in the analysis had Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 19 publications
3
36
2
2
Order By: Relevance
“…Sofosbuvir and simeprevir was well-tolerated, resulting in a sustained viral response for 12 weeks (SVR12) of 74% and 100% in patients with genotype 1a and 1b, respectively (8). In a multicenter study (9) with the same regimen in decompensated and compensated patients reported an SVR12 of 74% and 91%, respectively.…”
Section: Sofosbuvir-based Therapymentioning
confidence: 99%
“…Sofosbuvir and simeprevir was well-tolerated, resulting in a sustained viral response for 12 weeks (SVR12) of 74% and 100% in patients with genotype 1a and 1b, respectively (8). In a multicenter study (9) with the same regimen in decompensated and compensated patients reported an SVR12 of 74% and 91%, respectively.…”
Section: Sofosbuvir-based Therapymentioning
confidence: 99%
“…Buna karşılık siklosporinle birlikte kullanımı SMV'nin plazma konsantrasyonunda anlamlı artışla ("hepatic uptake transporter" inhibisyonu nedeniyle) sonuçlanmaktadır ve bu nedenle bu ilaçların birlikte kullanımı önerilmemektedir (39,67,92,93). DEA ilaçlarla antiretroviral (Tablo 5), narkotik (Tablo 6), kardiyovasküler (Tablo 7), lipid metabolizmasını etkileyen (Tablo 8), santral sinir sistemine etkili (Tablo 9) ve immünosüpresif (Tablo 10) ilaçlar arasındaki etkileşimler ilgili tablolarda özet-lenmiştir.…”
Section: Asunaprevir Ve Daklatasvirunclassified
“…Simeprevir undergoes oxidative metabolism from the CYP3A system (high interaction with drugs that suffer this metabolism) and subsequent excretion into the bile may cause jaundice and the elevation of ALT. In coinfection, HIV-HCV (only genotype 1) simeprevir should be used with antiretroviral drugs with which it does not have clinically significant interactions: abacavir, emtricitabine, enfuvirtide, lamivudine, maraviroc, raltegravir (and probably dolutegravir), rilpivirine, and tenofovir [44].…”
Section: Simeprevir (Olysio®-janssen)mentioning
confidence: 99%